Isolated and (in)voluntary “de-isolated” through their languages: two seemingly opposite cases - Camargo Souza, Livia (2021)
This paper consists of two first-person reports of linguists working in the documentation of endangered languages. We narrate two opposite situations: that of Guató, a language with only two speakers, survivors of a long process of colonization, and that of the language spoken by the Xinane people, a monolingual recently-contacted group.We make use of these two examples to problematize the concept of "isolation": the Xinane situation is, in fact, one of de-isolation (contact), carefully planned and executed by young people, after three generations of isolation motivated by white violence. Vicente, on the other hand, one of the two last rememberers of the guató language can be more literally characterized as one of voluntary isolation, despite the 400 years of contact of his fragmented people. We also discuss the challenges of creating fieldwork methodologies in these two extremely contrastive contexts of language vitality.